Population ageing: crisis or opportunity? - John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Population ageing reduces the working population relative to the number of pensions by one-third over next 30 years. The challenge presented by this development is how best to support pensioners incomes without suppressing the net incomes of the working population and capital accumulation too much. The ability of private savings and occupational pensions to meet this challenge is doubtful. There is a related issue of inter-generational equity: how do we share the burden of population ageing between generations, rather than passing it on to future generations. Given the uncertainty about future demographic and economic developments, it is important to have adaptable or self-correcting policies to address population ageing.
Keywords: 330